Investigating the analgesic effects of combined diphenhydramine and dipyrone in mice - Mostafa Kalantari; Firouz Faedmaleki; Arya Soneishargh (Veterinary and Comparative Biomedical Research)
Pain relief is a crucial aspect of modern surgery. The analgesic used should possess strong analgesic properties, a rapid onset of action, and minimal side effects to effectively reduce pain during and after surgical procedures. Therefore, the aim of the present study was to evaluate the analgesic effects of diphenhydramine and dipyrone (metamizole) in mice. For this study, 30 mice were randomly divided into five groups: the control group received normal saline; the standard group received 10 mg/kg morphine; treatment group 1 received 2.5 mg/kg diphenhydramine; treatment group 2 received 2.5 mg/kg dipyrone; and treatment group 3 received 2.5 mg/kg diphenhydramine combined with 2.5 mg/kg dipyrone. After injection, pain was assessed using the hot plate test and the formalin test. The results from both tests indicated that the combined use of dipyrone and diphenhydramine produced significant analgesic effects. Additionally, neither dipyrone (metamizole) nor diphenhydramine exhibited any side effects. Therefore, the use of dipyrone (metamizole) and diphenhydramine is recommended for safer surgical procedures.